Azerbaijani adaptation of the WHO-5 wellbeing index: investigating its relationship with psychological distress, resilience, and life satisfaction - Aliyev, Bakhtiyar; Rustamov, Elnur; Satici, Seydi Ahmet; Nuriyeva, Ulkar Zalova (SPRINGERNATURE, 2024)
BackgroundThe WHO-5 Wellbeing Index is a widely used tool for assessing psychological well-being. Despite its global application, its adaptation and validation for the Azerbaijani population had not been previously explored. This study aims to fill this gap by adapting the WHO-5 Wellbeing Index for Azerbaijani adults and examining its relationship with psychological distress, resilience, and life satisfaction.MethodsA sample of 875 Azerbaijani adults aged 18 to 89 (mean age = 29.13, SD = 10.98) participated in this study. The adaptation process included confirmatory factor analysis to test the original 5-item structure of the index in the Azerbaijani context. Additionally, item response theory analysis was employed to evaluate the discriminative values of the items. Reliability was assessed through various methods, including Cronbach's alpha, McDonald's omega, and Guttmann's lambda.ResultsConfirmatory factor analysis supported the original 5-item structure of the WHO-5 Wellbeing Index for the Azerbaijani sample, demonstrating alignment with the index's original version. All items showed acceptable discriminative values in item response theory analysis. The index also exhibited sufficient reliability, as evidenced by Cronbach's alpha, McDonald's omega, and Guttmann's lambda. Correlation and network analyses indicated significant associations of the WHO-5 Wellbeing Index with psychological distress, resilience, and life satisfaction. Specifically, the index was negatively correlated with depression, anxiety, and stress, and positively correlated with resilience and life satisfaction.ConclusionThe findings suggest that the WHO-5 Wellbeing Index is a valid and reliable tool for assessing psychological well-being in the Azerbaijani population. Its significant associations with psychological distress, resilience, and life satisfaction further affirm its utility in this cultural context.
Keywords: Wellbeing; Distress; Resilience; Scale adaptation; SCALE; VALIDATION; PEOPLE; IMPACT; Psychology